Record Keeping and Financial Performance of Fincom, Kololo Kampala Uganda - Abdallah Wakabenga (Uganda Christian University, 2025)
This study investigated the relationship between record keeping and financial performance at FINCOM, a financial institution located in Kololo, Kampala, and Uganda. The main objectives were to examine the types of record keeping systems used, assess the quality and consistency of financial records, and evaluate how record keeping affects financial performance. A descriptive research design was used, and data was collected through questionnaires from 104 employees across various departments. The findings showed that most of the employees at FINCOM use computerized systems like accountiThis study investigated the relationship between record keeping and financial performance at FINCOM, a financial institution located in Kololo, Kampala, Uganda. The main objectives were to examine the types of record keeping systems used, assess the quality and consistency of financial records, and evaluate how record keeping affects financial performance. A descriptive research design was used, and data was collected through questionnaires from 104 employees across various departments. The findings showed that most of the employees at FINCOM use computerized systems like accounting software and Excel spreadsheets, although some still use manual methods. The quality of financial records was rated as generally high, and most respondents agreed that proper record keeping helped improve budgeting, increase profits, and support better decision-making. A Pearson correlation analysis showed a strong and positive relationship between record keeping quality and financial performance, confirming that better records lead to better financial outcomes. The study concluded that record keeping is a key factor in financial success. It recommended that FINCOM fully transition to digital systems, standardize record keeping practices across all departments, and regularly train staff on proper financial documentation. Limitations of the study included its focus on only one organization and the use of self-reported data. The research provides useful insights for financial institutions aiming to improve their performance through better record keeping. Future studies could explore the role of employee training, regulatory compliance, and customer satisfaction in relation to financial record management. software and Excel spreadsheets, although some still use manual methods. The quality of financial records was rated as generally high, and most respondents agreed that proper record keeping helped improve budgeting, increase profits, and support better decision-making. A Pearson correlation analysis showed a strong and positive relationship between record keeping quality and financial performance, confirming that better records lead to better financial outcomes. The study concluded that record keeping is a key factor in financial success. It recommended that FINCOM fully transition to digital systems, standardize record keeping practices across all departments, and regularly train staff on proper financial documentation. Limitations of the study included its focus on only one organization and the use of self-reported data.